Systematic review on health care for transvestites and transsexuals in Brazil - Lima, Rafael Rodolfo Tomaz de; Flor, Taiana Brito Menêzes; Noro, Luiz Roberto Augusto (Revista de Saúde Pública, 2023)
OBJECTIVE: To synthesize scientific evidence to characterize health care for transvestites and transsexuals in Brazil. METHODS: This is a systematic review, conducted from July 2020 to January 2021 and updated in September 2021, whose protocol is registered in the International Prospective Register of Systematic Reviews (PROSPERO) platform, under code CRD42020188719. The survey of evidence was carried out in four databases and eligible articles were evaluated for methodological quality, and those with a low risk of bias were included. RESULTS: Fifteen articles were selected and the findings were grouped into six categories according to their thematic approaches: Possibilities to transform health care; Transvestiphobia and transphobia: violations inside and outside the Brazilian Unified Health System (SUS); Professional unpreparedness to care for transvestites and transsexuals; Search for health care alternatives; Right to health for transvestites and transsexuals: utopia or reality?; The Transsexualization Process: advances and challenges. CONCLUSIONS: There is evidence that health care for transvestites and transsexuals in Brazil is still exclusive, fragmented, centered on specialized care and guided by curative actions, resembling the care models that preceded the SUS and which have been heavily criticized since the Brazilian Sanitary Reform.